Reproducibility and Validity of a Stroke Effectiveness Test in Table Tennis Based on the Temporal Game Structure - Belli, Taisa; Misuta, Milton Shoiti; de Moura, Pedro Paulo Ribeiro; Tavares, Thomas dos Santos; Ribeiro, Renê Augusto; Santos, Yura Yuka Sato dos; Sarro, Karine Jacon; Galatti, Larissa Rafaela (Frontiers in Psychology, 2019)
Purpose: This study aimed to develop a stroke effectiveness test in table tennis based on the temporal game structure to assess the ball speed and ball placement of the players, with a purpose to analyze its reproducibility and validity. Methods: Nineteen male table tennis players participated in this study. The test was performed twice during the first session and once during the second session to assess the intrasession and intersession reproducibility, respectively. Moreover, the test was examined on its ability to discriminate between regional (n=10) and local performance-level (n=9) players and on the relationship between the test results and the table tennis performance to assess the discriminant and concurrent validity, respectively. In general, the test consisted of 11 simulated rallies of 2–5 balls with the effort and rest ratio of 0.5, and focused on attack with offensive strokes at defensive balls delivered by a robot randomly between the left and right positions on the table. Results: Ball speed, ball placement, and ball speed-ball placement index showed satisfactory reliability (ICC range 0.78–0.96, P <0.05) and agreement (CV range 2.7–16.2%) outcomes. Additionally, the Bland-Altman plots show the systematic error of the analyses closer to 0, and that most values were within the limits of agreements. Concerning validity analyses, regional players had higher scores of ball placement (+51.3%; P = 0.01, ES = 1.33) and ball speed-ball placement index (+56.1%; P = 0.0009, ES = 1.87) as well as made fewer errors (-25.4%; P = 0.017, ES = 1.20) than local players. Moreover, ball placement (r = - 0.79, P = 0.04), ball speed-ball placement index (r = - 0.78, P = 0.04), and percentage error (r = 0.88, P = 0.01) presented a strong and significant correlation with table tennis performance. However, ball speed was slightly different between the regional than local players (+1.7%; P = 0.78, ES = 0.13) and this variable was not related to table tennis performance (r = 0.32, P = 0.49). Conclusion: Our findings show evidences that the test is reproducible. Moreover, discriminant and concurrent validity are confirmed for ball placement and ball speed-ball placement index.